EVALUASI KEBIJAKAN PENYEDIAAN DAN PENGELOLAAN RUANG TERBUKA HIJAU DALAM MENDUKUNG KABUPATEN SEHAT DAN LAYAK ANAK: STUDI KASUS KABUPATEN MOJOKERTO - Ferina, Anggia Citra Okta; Megawati, Suci (Universitas Negeri Surabaya, 2025)
This study aims to evaluate the policy of providing and managing Green Open Spaces (GOS) in Mojokerto Regency as part of the strategy to achieve a Healthy Regency and a Child-Friendly Regency. This qualitative research applies a literature study method, primarily referring to the document Study of Standard Service Facilities for Village Park RTH in Mojokerto Regency 2024. The findings reveal that most village parks do not meet the technical standards stipulated in Ministerial Regulation ATR/BPN No. 14 of 2022 and Ministerial Regulation of Women Empowerment and Child Protection No. 12 of 2022, particularly regarding minimum area, child-friendly play facilities (RBRA), and supporting elements such as sanitation, lighting, and protective vegetation. On the other hand, parks actively managed by village-owned enterprises (BUMDes), such as Ghanjaran Park, demonstrate the importance of multi-stakeholder collaboration in improving RTH quality and generating local economic value. However, challenges remain in cross-sector coordination, community participation, and the integration of health and child-friendly indicators in open space planning. This study recommends strengthening technical regulations, increasing community involvement, and developing culturally themed parks as part of an inclusive and sustainable public space development strategy.